Chronic obstructive pulmonary disease new pharmacological treatments and their relationship with cardiovascular effects - Dávil, Luis P.; Guillen Gallardo, Erika; Loaiza, Francisca A.; Espinosa, Alisson Valladares; Torres, André Valenzuela; Vásquez, Johanna Lisbeth; Pérez, Deysi Carolina Silva (International Journal of Research in Medical Sciences, 2025)
Chronic obstructive pulmonary disease (COPD) is considered a progressive inflammatory condition that is often complicated by one or more cardiovascular diseases (CVD). This review explores the cardiovascular impacts of current anti-inflammatory therapies that have shown high relevance in COPD. Phosphodiesterase (PDE) inhibitors may offer anti-inflammatory effects with improved lung function, but may produce cardiac arrhythmias when PDE3 is inhibited, although PDE4 inhibitors reduce cardiovascular events by improving endothelial function and reducing thrombosis. Similarly, p38 mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) inhibitors target COPD-related inflammation and may benefit patients with COPD and CVD. p38 MAPK inhibitors reduce cardiac fibrosis, improve contractility, and reduce arrhythmia risk. PI3K inhibitors target the PI3K/Akt pathway, which drives atherosclerosis and cardiac fibrosis, and thus potentially mitigate both plaque instability and fibrosis. Biologic therapies, including monoclonal antibodies that inhibit IL-5, IL-13/IL-4, thymic stromal lymphopoietin, IL-33, and IL-17A, are promising in reducing exacerbations, but require tight cardiovascular monitoring due to their immunomodulatory effects. Single-target inhibitors of neutrophil elastase or matrix metalloproteinases show limited efficacy in COPD, but may help cardiovascular patients by stabilizing atherosclerotic plaques by promoting vascular smooth muscle cell proliferation. Alpha-1 antitrypsin replacement therapy is promising, potentially reducing COPD exacerbations and providing cardiovascular protection, especially in myocardial injury.